Improving student achievement by using interactive Learning model of ips lesson in natural appearance At the first grade students of sd negeri 43 siguntur in Academic year 2015/2016 - Yuspi Yuspi (Fakultas Sastra Universitas Ekasakti, 2017)
The purpose of this study is to prove that the use of the environment around the school to enhance students' understanding of the events of Islamic religious education in students of Class I V In S D Affairs No. 43 Siguntur Young. This study uses a class action approach. The study population was taken of all students in grade IV , the data collection techniques used artificial teacher learning achievement test. Actions performed a total of two cycles. Data analysis techniques used analysis of the percentage of change in the results of the evaluation study before and after tutoring services with peer tutors. Thus there is an increasing mastery learning students from the first cycle to the second cycle. Based on the above, it can be made a conclusion as follows: